Drug utilization review of general anaesthetic agents in a tertiary care hospital - Gomathi, G.; Yadav, Ghanshyam; Pandey, B. L. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug utilization review plays a key role in helping the healthcare system to understand, interpret and improve the prescribing, administration and use of medications. The principle aim of drug utilization review was to facilitate rational use of drugs, which implies the prescription of a well documented drug in an optimal dose on the right indication. Methods: An observational study of anaesthetic practice was carried out in the department of Anaesthesiology in tertiary care hospital, Varanasi after approval from institutional ethical committee. The data of patients who underwent surgery under general anaesthesia were collected in predesigned patient profile form and were analyzed for drug utilization review. Results: 110 patients were enrolled with mean age 35.30±17.99 years and mean weight 51.32±15.32kg. Laparoscopic cholecystectomy (43.63%), otorhinolaryngology surgeries (36.36%), cardiothoracic vascular surgery (4.54%), neurosurgery (4.54%) and other surgeries (10.93%) required general anaesthetic agents were reviewed. Propofol (93.63%) and etomidate (6.36%) were used for induction of anaesthesia. Propofol (45.45%), isoflurane (53.63%), sevoflurane (0.90%) were administered for maintenance of anaesthesia in various surgeries. Adverse outcomes observed were hypotension (7.27%), bradycardia (6.36%), hypertension (3.63%) and post operative nausea and vomiting (PONV) (2.72%). Conclusions: Propofol is most commonly prescribed drug for induction of anaesthesia. Isoflurane is most commonly prescribed inhalational anaesthetic agent for maintenance of anaesthesia followed by Propofol. Hypotension is most common adverse outcome observed.